Constructing of Analysis Mathematical Model for Stream Cipher Cryptosystems - Naser , Ayad Ghazi; Majeed , Fatin A. H. (Iraqi Journal of Science, 2022)
The aim of this paper is to construct the analysis mathematical model for stream cipher cryptosystems in order to be cryptanalysis using the cryptanalysis tools based on plaintext attack (or part from it) or ciphertext only attack, choosing Brüer generator as study case of nonlinear stream cipher system.The constructing process includes constructing the linear (or non-linear) equations system of the attacked nonlinear generator. The attacking of stream cipher cryptosystem means solving the equations system and that means finding the initial key values for each combined LFSR.